Podborer (Helicoverpa armigera Hubn.) does not show specific adaptations in gut proteinases to dietary Cicer arietinum Kunitz proteinase inhibitor - Srinivasan, A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Gatehouse, J. A.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
We investigated the response of Helicoverpa armigera larvae towards ingestion of Cicer arietinum Kunitz proteinase inhibitor (CaKPI), which caused antagonistic effects on developing H. armigera larvae. CaKPI-degrading proteinases were not detectable in either control or sensitized larvae. There were negligible increases in total proteinase activity, as well as in trypsin-like and chymotrypsin-like activities of H. armigera gut proteinases (HGPs). Decrease in sensitivity of HGPs to inhibition by CaKPI was not observed when the inhibitor was fed Suggesting that the insect had not shown a specific adaptive response to dietary CaKPI. Semi-quantitative reverse transcriptase polymerase chain reaction (Q RT-PCR) analysis showed a general up-regulation of proteases in larvae that ingested CaKPI and a specific regulation of individual transcripts was not observed. CaKPI had maximum inhibitory activity against HGP derived from fourth instar larvae. CaKPI was equally potent in inhibition of HGPs derived from larvae fed on different host plants, as well as various proteinase inhibitors (Pis) to which larval adaptation was previously reported. The lack of larval response to CaKPI was attributable to the atypical active site sequence and inhibitory activity of CaKPI and/or to the pre-adaptation of H. armigera larvae due to the constant exposure to basal levels of CaKPI in chickpea seeds or a chickpea seed-based diet. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cicer arietinum; Helicoverpa armigera; insect response; proteinase; Proteinase inhibitor

Phylogeographical studies in disjunct populations of symplocos laurina wall. using cytoplasmic PCR-RFLP approach - Banu, Sofia; Lagu, Meena D.; Gupta, Vidya S. (Tree Genetics & Genomes, 2010)
Genetic variation, haplotype relationships, and potential regions of diversity in Symplocos laurina Wall. (Symplocaceae), a montane tree species from India, have been tested using molecular and biogeographical data to infer phylogeographic patterns. The polymerase chain reaction-restriction fragment length polymorphism technique was used to determine the chloroplast (cp) and mitochondrial (mt) DNA haplotypes of 218 individuals from 12 populations, collected from Northeast India (NEI), which is a part of Indo-Burma biodiversity hotspot, and South India, which includes the Western Ghats (WG), another biodiversity hotspot from India and Eastern Ghats (EG). Nine cpDNA (chlorotypes) and 24 mtDNA haplotypes (mitotypes) were identified; the WG region was identified as the most diverse for chlorotypes and the NEI region for mitotypes. Although a strong population differentiation was observed, phylogeographic structure was found to be absent for both the genomes. The haplotype network revealed the presence of two main lineages: NEI-WG lineage and EG lineage, largely without overlapping distributions. The study tests two hypotheses, namely vicariance and dispersal, to understand the distribution of plants in India. The population structure of S. laurina strongly suggests the persistence of the species in putative refugial areas preglaciation and further establishment of other populations of S. laurina from these refugial populations.
Keywords: Cytoplasmic genome; Genetic diversity; Phylogeography

Phylogenomic analysis of UDP glycosyltransferase 1 multigene family in Linum usitatissimum identified genes with varied expression patterns - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Gupta, Vidya S. (BMC Genomics, 2012)
Background: The glycosylation process, catalyzed by ubiquitous glycosyltransferase (GT) family enzymes, is a prevalent modification of plant secondary metabolites that regulates various functions such as hormone homeostasis, detoxification of xenobiotics and biosynthesis and storage of secondary metabolites. Flax (Linum usitatissimum L.) is a commercially grown oilseed crop, important because of its essential fatty acids and health promoting lignans. Identification and characterization of UDP glycosyltransferase (UGT) genes from flax could provide valuable basic information about this important gene family and help to explain the seed specific glycosylated metabolite accumulation and other processes in plants. Plant genome sequencing projects are useful to discover complexity within this gene family and also pave way for the development of functional genomics approaches. Results: Taking advantage of the newly assembled draft genome sequence of flax, we identified 137 UDP glycosyltransferase (UGT) genes from flax using a conserved signature motif. Phylogenetic analysis of these protein sequences clustered them into 14 major groups (A-N). Expression patterns of these genes were investigated using publicly available expressed sequence tag (EST), microarray data and reverse transcription quantitative real time PCR (RT-qPCR). Seventy-three per cent of these genes (100 out of 137) showed expression evidence in 15 tissues examined and indicated varied expression profiles. The RT-qPCR results of 10 selected genes were also coherent with the digital expression analysis. Interestingly, five duplicated UGT genes were identified, which showed differential expression in various tissues. Of the seven intron loss/gain positions detected, two intron positions were conserved among most of the UGTs, although a clear relationship about the evolution of these genes could not be established. Comparison of the flax UGTs with orthologs from four other sequenced dicot genomes indicated that seven UGTs were flax diverged. Conclusions: Flax has a large number of UGT genes including few flax diverged ones. Phylogenetic analysis and expression profiles of these genes identified tissue and condition specific repertoire of UGT genes from this crop. This study would facilitate precise selection of candidate genes and their further characterization of substrate specificities and in planta functions.

Proteome profiling of flax (linum usitatissimum) seed: characterization of functional metabolic pathways operating during seed development - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Journal of Proteome Research, 2012)
Flax (Linum usitatissimum L.) seeds are an important source of food and feed due to the presence of various health promoting compounds, making it a nutritionally and economically important plant. An in-depth analysis of the proteome of developing flax seed is expected to provide significant information with respect to the regulation and accumulation of such storage compounds. Therefore, a proteomic analysis of seven seed developmental stages (4, 8, 12, 16, 22, 30, and 48 days after anthesis) in a flax variety, NL-97 was carried out using a combination of ID-SDS-PAGE and LC-MSE methods. A total 1716 proteins were identified and their functional annotation revealed that a majority of them were involved in primary metabolism, protein destination, storage and energy. Three carbon assimilatory pathways appeared to operate in flax seeds. Reverse transcription quantitative PCR of selected 19 genes was carried out to understand their roles during seed development. Besides storage proteins, methionine synthase, RuBisCO and S-adenosylmethionine synthetase were highly expressed transcripts, highlighting their importance in flax seed development. Further, the identified proteins were mapped onto developmental seed specific expressed sequence tag (EST) libraries of flax to obtain transcriptional evidence and 81% of them had detectable expression at the mRNA level. This study provides new insights into the complex seed developmental processes operating in flax.
Keywords: alpha-linolenic acid; carbon flux; Digital expression analysis; flax seed development; MSE; secoisolariciresinol diglucoside

Plasticity of protease gene expression in helicoverpa armigera upon exposure to multi-domain capsicum annuum protease inhibitor - Mahajan, Neha S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica et Biophysica Acta (BBA) - General Subjects, 2013)
Background A multi-domain Pin-II type protease inhibitor from Capsicum annuum (CanPI-7) is known to be effective against the insect pest, Helicoverpa armigera. The present study is an attempt to investigate the optimal dose of recombinant CanPI-7 (rCanPI-7) for effective antibiosis to H. armigera and further to characterize the responses of digestive proteases upon rCanPI-7 ingestion. Methods The gut protease activity was assessed biochemically and transcript accumulation pattern for selected trypsin and chymotrypsin genes was analyzed by quantitative Real-Time PCR. Results The growth retardation upon exposure to rCanPI-7 was more prominent in neonates as compared to third instar larvae. Influence of stage and dosage of rCanPI-7 was conspicuous on the expression and regulation of candidate trypsin and chymotrypsin genes in H. armigera. The transcript accumulation pattern correlated with the protease activity in rCanPI-7 exposed larvae. Conclusions We conclude that early exposure and specific dose of protease inhibitor are essential for effective antibiosis despite the large diversity and plasticity in the expression of protease genes in H. armigera. Moreover, it is also evident that the regulation and expression of H. armigera gut proteases are specific to the stage of PI exposure. General significance These results highlight the requirement of optimal PI concentration for effective growth retardation and for inhibiting the major gut proteases of H. armigera.

Population genetic and phytochemical dataset of Saraca asoca: a traditionally important medicinal tree - Hegde, Satisha; Pai, Sandeep Ramchandra; Bhagwat, Rasika M.; Sainia, Archana; Rathore, Poonam Kanwar; Jalalpure, Sunil Satyappa; Hegde, Harsha Vasudev; Sugunan, Attayoor Purushottaman; Gupta, Vidya S.; Kholkute, Sanjiva D.; Roy, Subarna (Data in Brief, 2019)
The data presented in this article is in support of the research paper “Genetic and phytochemical investigations for understanding population variability of the medicinally important tree Saraca asoca to help develop conservation strategies” Hegde et al., 2018. This article provides PCR based Inter-Simple Sequence Repeat (ISSR) and HPLC datasets of 106 individual samples of Saraca asoca collected from various geographical ranges of the Western Ghats of India. The ISSR data includes information on genetic diversity and images of population structures generated through amplified DNA products from samples of Saraca asoca leaf. Phytochemical data obtained from HPLC includes concentration (mg/g) of gallic acid (GA), catechin (CAT), and epicatechin (EPI). The data also presents information obtained from various statistical analysis viz. standard error of the mean values, distribution variables, prediction accuracy, and multiple logistic regression analysis.